Money supply in Russian Federation: the analysis of monetary aggregates and their influence on the inflation - A. A. Uryupina (Vestnik MGIMO-Universiteta)
The money supply growth is one of the main factors responsible for inflation in Russian Federation. The article examines the money supply in Russia in the past few years: the evolution, structure and other characteristics of monetary aggregates and how the growth of monetary aggregates effects the price level in Russia.